Concession Bidding Rules and Investment Time Flexibility - Michele Moretto; Cesare Dosi (Fondazione Eni Enrico Mattei (FEEM), 2007)
We study the competition to operate an infrastructure service by developing a model where firms report a two-dimensional sealed bid: the price to consumers and the concession fee paid to the government. Two alternative bidding rules are considered in this paper. One rule consists of awarding the exclusive right of exercise to the firm that reports the lowest price. The other consists of granting the franchise to the bidder offering the highest fee. We compare the outcome of these rules with reference to two alternative concession arrangements. The former imposes the obligation to immediately undertake the investment required to roll-out the service. The latter allows the winning bidder to optimally decide the investment time. The focus is on the effect of bidding rules and managerial flexibility on expected social welfare. We find that the two bidding rules provide the same outcome only when the contract restricts the autonomy of the franchisee, and we identify the conditions under which time flexibility can provide a higher social value.
Keywords: L51; D44; D92; 330; Concessions; Auctions; Bidding Rules; Managerial Flexibility; Konzession; Auktionstheorie; Theorie